New emerging targets in cancer immunotherapy: the role of VISTA. (18th June 2020) - Tagliamento, Marco; Bironzo, Paolo; Novello, Silvia
Abstract : The immune surveillance system is complex and regulated by different actors. Programmed death protein-ligand 1 (PD-L1), the only approved biomarker in clinical practice, has proven to be imperfect in selecting patients to immune checkpoint inhibitors treatment. Therefore, new biomarkers, and new therapeutic targets, are needed to maximise the efficacy of immunotherapy. V-domain Ig Suppressor of T-cell Activation (VISTA) is a programmed death protein-1 (PD-1) homolog expressed on T cells and on antigen-presenting cells, which regulates processes of activation and repression of the immune system with not yet completely clarified mechanisms. Its blockage has demonstrated in vitro and in vivo antitumour activity. The clinical research of VISTA antagonists is ongoing. Particularly, CA-170, an orally delivered dual inhibitor of VISTA and PD-L1, has shown to have clinical efficacy in phase I and II clinical trials in different advanced solid tumour types. Further data are needed to define whether this drug class can become a new therapeutic option for patients with VISTA expressing cancers.